From Outbreaks to Artificial Intelligence: A Comprehensive Review of Monkeypox Virus Epidemiology, Diagnosis, Treatment, Vaccination, and Deep Learning Applications - Shahed Ahmadi; Mahdi Amirzadeh; Mousa Ahmadi; Saeed Soleiman-Meigooni (Journal of Tropical Medicine)
Conclusion: This review highlights the importance of using traditional public health knowledge alongside modern AI to manage MPOX outbreaks effectively. It shows that we need strong public health policies, focused interventions, and ongoing research on how AI can help control infectious diseases.